KECERDASAN EMOSIONAL MAHASISWA AKADEMI KEPERAWATAN BINA SEHAT PPNI MOJOKERTO - Indatul Laili, Siti (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Every adolescents is equipped with emotion to offset ratios tend to act based on the principles of logic. Emotional aspect would lead adolescents to consider various aspects before acting. The purpose of this research was to determine the emotional quotient one semester students Akademi Keperawatan Bina Sehat PPNI Mojokerto. The research design used descriptive. The sampel was some of one semester students Akademi Keperawatan Bina Sehat PPNI Mojokerto a number of 18 respondents with simple random sampling teckhnic. The data was taken by a questionnaire. Analyzing data used was Microsoft Office Excel 2007. Research result was 18 respondents (77.8%) with a high emotional quotient category. Students have high emotional quotient category able to realize emotions appropriately, capable of implanting, and able to understand any changes little emotion.Keyword:Emotional Quotient, Adolescents